Using System Architecture Maturity Artifacts to Improve Technology Maturity Assessment - Sarfaraz, Matin; Sauser, Brian J.; Bauer, Edward W. (Procedia computer science, 2012)
The Technology Readiness Level (TRL) is a measurement used to assess the maturity of a technology prior to its inclusion in a system. It is a management tool utilized by program managers, project managers, and others in acquisition management to assess technology maturity. The TRL of a technology is determined by the assessment of Subject Matter Experts (SMEs) who examine the degree to which a criteria is being fulfilled. One of the current deficiencies in using TRLs is the subjectivity in determining the readiness value. This paper aims to reduce subjectivity in TRL maturity assessments by utilizing the maturity artifacts present in system architecture models. This paper will propose a technique and research methodology that can support TRL in technology maturity assessment in the design and development phase of a technology lifecycle.